Penentuan Sebaran Reservoar Menggunakan Atribut Seismik Pada Lapangan “Cemara” Cekungan Sumatera Tengah, Riau - Zalwi, Eka Nadila; Namigo, Elistia Liza; Azlin, Amalia (Jurnal Fisika Unand, 2025)
A research has been carried out to determine the distribution of reservoirs in the "Cemara" Field, Riau using the seismic attribute method. The data used is secondary data resulting from the acquisition of PT. Bumi Siak Pusako in the form of 3D Post-Stack Time Migration (PSTM) seismic data and well data. Seismic attribute analysis is carried out by changing the original seismic volume into a sweetness seismic volume, then extracting the RMS (Root Mean Square), average energy and instantaneous frequency seismic attributes. The results of the RMS and average energy attribute map analysis show that the reservoir distribution area has a high amplitude with attribute values ​​of 2.0-3.2 and 7.0-11.00 respectively, which are high values ​​for each attribute. The results of the instantaneous frequency attribute show that the reservoir distribution area is at low frequency with an attribute value of 12.5-0.00. The crossplot of the attribute with the net sandstone layer value shows a higher distribution of clean sandstone in the production well area. The cross plot of attributes with vshale values ​​shows lower values ​​in the production well area, indicating that the reservoir distribution around the production well has good porosity. The reservoir distribution zone is in the altitude zone with a depth of ± 1,830 feet in the west and northeast directions, represented by the sweetspot zone in the amplitude attribute.